Patriarchal Bargaining Strategies in The Secret Lives of Baba Segi’s Wives by Lola Shoneyin - Lorencia Sariani Tondang; Karina Hanum Luthfia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research examines the mechanisms of the patriarchal bargain within a polygamous household through a textual analysis of Lola Shoneyin’s novel The Secret Lives of Baba Segi’s Wives. Employing Deniz Kandiyoti’s framework of the "patriarchal bargain," this study aims to analyze how the absolute authority of the male head is maintained and subsequently negotiated by his four wives. The research utilizes a descriptive qualitative method with a systematic close reading approach. The findings indicate that the patriarchal system in Baba Segi's household operates through a rigid "rule of the game" that reduces a woman’s worth entirely to her reproductive function. This system strips childless women of their personal identity, comfort, and verbal rights. To survive these concrete constraints, the wives deploy bargaining strategies. First, the three senior wives, namely Iya Segi, Iya Tope, and Iya Femi, execute a Reproductive Strategy. They perform exaggerated domestic submission and flattery to mask their deliberate biological sabotage, secretly conceiving children with other men to secure material safety and social prestige. Second, the educated fourth wife, Bolanle, deploys an Intellectual Resistance Strategy. Utilizing her higher education and critical reasoning, Bolanle rejects traditional, irrational solutions and shifts the domestic battleground to a modern medical institution. Under the authority of science, she successfully exposes the husband's infertility, thereby dismantling the false premise of absolute male supremacy. This research concludes that the characters in the novel are strategic actors who actively exploit the blind spots of patriarchal power. The patriarchal bargain does not merely limit women's options, but also provides distinct avenues for active subversion, proving that women will systematically leverage their specific modalities whether interpersonal deceit or intellectual capacity to destabilize masculine dominance.